Effect of silica fume and fly ash as cementitious material on hardened properties and embodied carbon of roller compacted concrete - Kumar, A. (Springer Science and Business Media Deutschland GmbH, 2022)
The production of cement releases an enormous amount of CO2 into the environment. Besides, industrial wastes like silica fume and fly ash need effective utilization to reduce their impacts on the environment. This research aims to explore the influence of silica fume (SF) and fly ash (FA) individually and combine them as binary cementitious material (BCM) on the hardened properties and embodied carbon of roller compacted concrete (RCC). A total of ten mixes were prepared with 1:2:4 mix ratio at the different water-cement ratios to keep the zero slump of roller compacted concrete. However, the replacement proportions for SF were 5â15, and FA were 5â15 by the weight of cement individually and combine in roller compacted concrete for determining the hardened properties and embodied carbon. In this regard, several numbers of concrete specimens (cubes and cylinders) were cast and cured for 7 and 28 days correspondingly. It was observed that the compressive strength of RCC is boosted by 33.6 MPa and 30.6 MPa while using 10 of cement replaced with SF and FA individually at 28 days, respectively. Similarly, the splitting tensile strength of RCC is enhanced by 3.5 MPa at 10 cement replaced with SF and FA on 28 days, respectively. The compressive and splitting tensile strength of RCC is increased by 34.2 MPa and 3.8 MPa at SF7.5FA7.5 as BCM after 28 days consistently. In addition, the water absorption of RCC decreased while using SF and FA as cementitious material individually and together at 28 days. Besides, the embodied carbon of RCC decreased with increasing the replacement level of SF and FA by the mass of cement individually and combined. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.